Fibrosarcoma with osseous-metaplasia: A rare case of neck tumor in a domestic fowl and its successful surgical removal - M. Madeena Begum; R. Thangathurai; Anisha J. Perumbilly; M. Balagangatharathilagar (The Indian Veterinary Journal, 2023)
An eight month old domestic fowl was brought to the hospital with the history of huge mass on the neck. On further enquiry, the owner reported that the mass was first noticed six months back and it gradually increased in size as the days progressed. On physical examination, a hard spherical shaped mass was noticed on the caudal portion of the neck just above the crop. On palpation, no pain was evinced and the mass was freely moving under the skin. Fine needle aspiration cytology (FNAC) revealed Fibrosarcoma. Under general analgesia, tumor excision was done and the mass was sent for histopathological analysis. The result confirmed the case as fibrosarcoma with osseous-metaplasia. Post operatively, the animal was maintained with antibiotic and wound management. Suture was removed on 7th postoperative day. The bird made an uneventful recovery.